Es ward Frühling 1848 : Bilder aus einem großen Jahr - Victor, Walther 1895-1971 (Aufbau-Verl, 1948)
Margaret Fuller; George Sand; Lola Montez; Heinrich Heine; Ferdinand Freiliggrath; Karl Marx; Friedrich Engels